Transient HCl in the atmosphere of Mars - Korablev, O; Olsen, KS; Trokhimovskiy, A; Lefèvre, F; Montmessin, F; Fedorova, AA; Toplis, MJ; Alday, J; Belyaev, DA; Patrakeev, A; Ignatiev, NI; Shakun, AV; et al. (American Association for the Advancement of Science, 2021)
A major quest in Mars' exploration has been the hunt for atmospheric gases, potentially unveiling ongoing activity of geophysical or biological origin. Here, we report the first detection of a halogen gas, HCl, which could, in theory, originate from contemporary volcanic degassing or chlorine released from gas-solid reactions. Our detections made at ~3.2 to 3.8 μm with the Atmospheric Chemistry Suite and confirmed with Nadir and Occultation for Mars Discovery instruments onboard the ExoMars Trace Gas Orbiter, reveal widely distributed HCl in the 1- to 4-ppbv range, 20 times greater than previously reported upper limits. HCl increased during the 2018 global dust storm and declined soon after its end, pointing to the exchange between the dust and the atmosphere. Understanding the origin and variability of HCl shall constitute a major advance in our appraisal of martian geo- and photochemistry.